PENGUKURAN KESEHATAN KEUANGAN PERUSAHAAN ASURANSI DAN PERUSAHAAN REASURANSI BERDASARKAN METODE RISK BASED CAPITAL (RBC) - Komdax, Johan (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2013)
Insurance business is one of the types of business activities that involve risk. Risks faced by insurance companies and reinsurance companies can be sourced from financial performance, market conditions, and the type of business being operated. To improve oversight of the financial performance of insurance companies and reinsurance companies in Indonesia, the finance minister has issued regulation No. 53 I PMK.OJO I 2012 on the financial health of insurance companies and reinsurance companies. The purpose of that rule is to protect customer fonds contained in the insurance companies and reinsurance companies in order to stay safe, and can be used when there is a claim. This study uses the financial statements of insurance companies and reinsurance companies listed in Indonesia Stock Exchange (IDX) in 2012. The results showed that there are six insurance companies and one reinsurance company is healthy, whereas there are 3 insurance companies that are not healthy. For insurance companies that are not healthy, there are consequences that would come from the government, Bapepam-LK, customers, and investors.